The regional training centre for the emergency medical teams initiative in the WHO African region: a review of the development and progress over the past 4 years - Oyugi, Boniface; Martinez-Monterrey, Lazaro Gilberto; Ayalew, Leilina; Okeibunor, Joseph Chukwudi; Mbasha, Jerry-Jonas; Kamara, Rashidatu; Relan, Pryanka; Tadelle, Nahom; Gebreyesus, Alegnta; Zeynu, Neima; Salio, Flavio; Balde, Thierno; et al. (Frontiers in Public Health, 2025)
BackgroundA coherent and systematic approach to education and training of the workforce under the EMT initiative has been identified as an imperative step to improve the quality and professionalism of emergency response teams. On April 14 2021, the WHO and the Ethiopian Ministry of Health (MoH) jointly launched a training centre to enhance the delivery of emergency medical and health services in the continent when faced with humanitarian and other public health emergencies (PHEs).ObjectiveThis paper describes the development and progress of the EMT training centre in the WHO African Region over the past 4 years and elucidates its implementation processes. It further elucidates the lessons learned, including the complexities and challenges, and proposes recommendations for enhancing the centre’s future.MethodsThis descriptive retrospective study systematically documents the development and progress of the EMT training centre in the WHO African Region over the past 4 years. The study applied a mixed-methods qualitative approach through key informant interviews (KIIs) and document reviews. The study utilises the policy cycle framework as an analytical framework focusing on the EMT agenda setting (problem identification), formulation, adoption, implementation, and evaluation.ResultsThe concept emerged at the outset of the pandemic, driven by the need to establish a United Nations (UN) field hospital for evacuating UN staff. Addis Ababa was chosen for its strategic location, accessibility, and strong political support. However, the idea evolved into a training centre based on the decision not to include Addis Ababa in the UN staff safe and rapid patient transfer and medical evacuation (medevac) system. Following the scoping mission, the centre’s design and the training portfolio were done, and implementation started immediately following the joint official launch by the WHO and Ethiopian MoH. Since implementing the training centre concept, 12 countries in 2022 and 7 in 2023 benefited from different training out of the 10 countries prioritised at the onset. Continuous refinement of the procurement has happened throughout the implementation process. In October 2021, a comprehensive monitoring and evaluation framework with indicators and tracking timelines was developed at the inception of the training centre.ConclusionThe future of the centre will not only be limited to EMT but will also serve as a training centre capable of hosting various types of training and technical topics that could be useful, such as training on Rapid Response Teams (RRTs) and the WHO Regional Office for Africa (AFRO) AVoHC-SURGE initiative, simulations, etc. It is envisioned as a knowledge hub, a place where the region and the countries could work together to improve effectiveness of their activities and interoperability, develop communities of practice, generate research ideas, or share knowledge on documentation processes and existing resources.